1999
DOI: 10.1021/jp992752p
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Directed Adsorption in the Epitaxy Growth of Streptocyanine Dye Crystals

Abstract: The simple molecular structure, relatively high stability, and color variation with molecular packing structure make the streptopolymethine dyes an ideal candidate for the study of surface effects on the nucleation and growth of organic crystals at a liquid/solid interface. In situ optical and atomic force microscopy (AFM) experiments were conducted on amorphous glass and crystalline muscovite mica in order to correlate the crystal morphology and orientation with early molecular events during adsorption and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The IPCE absorptance spectra in Figures and were simulated using a linear sum of the dicarboxylated cyanine dye monomer and H-aggregate absorbance spectra calculated in Figure b and d. Interestingly, in no case were J-aggregates observed in the IPCE spectra despite the well-known tendency for cyanine dyes to form J-aggregates. , The spectral fitting was in good agreement with the IPCE spectra for B4 (SI Figure S1), and G15 (SI Figure S2) dyes, however the spectral agreement was of lower quality for the B1 dye (Figure ). The B1 dye is unique among the four dicarboxylated cyanine dyes studied; the additional methylene spacer on the carboxylated appendage may afford the B1 dye more flexibility to bind to the TiO 2 surface.…”
Section: Resultsmentioning
confidence: 66%
“…The IPCE absorptance spectra in Figures and were simulated using a linear sum of the dicarboxylated cyanine dye monomer and H-aggregate absorbance spectra calculated in Figure b and d. Interestingly, in no case were J-aggregates observed in the IPCE spectra despite the well-known tendency for cyanine dyes to form J-aggregates. , The spectral fitting was in good agreement with the IPCE spectra for B4 (SI Figure S1), and G15 (SI Figure S2) dyes, however the spectral agreement was of lower quality for the B1 dye (Figure ). The B1 dye is unique among the four dicarboxylated cyanine dyes studied; the additional methylene spacer on the carboxylated appendage may afford the B1 dye more flexibility to bind to the TiO 2 surface.…”
Section: Resultsmentioning
confidence: 66%
“…Many studies of noncovalently bound cyanine dyes on surfaces have shown red-shifted or J-aggregation. 16,[25][26][27][28] The observation of a blue-shifted or H-aggregate type is less well-reported, although at high concentrations in solution these and similar dyes exhibit H-dimerization. 24 The "isotherm" for G7 illustrated in Figure 4b shows the contributions of dye monomers, dimers, and total adsorbed dye obtained from the fitting of the photocurrent spectrum at the various surface coverages.…”
Section: Resultsmentioning
confidence: 99%
“…the hydrophobic or van der Waals interactions between the aliphatic carbon chains or aromatic rings. As was demonstrated impressively by Daehne et al, aggregation also occurs for pure dialkylamino-polymethine chains [33,34]. For most of the dyes forming J-aggregates in aqueous solutions, the morphology and structure of the aggregates are unknown.…”
Section: Water Soluble Amphiphilic Carbocyanine Dyesmentioning
confidence: 97%